Molasses-fat blend as an energy source and conditioning agent in feedlot diets - Flake, A.S.; Kuhl, Gerry L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two yearling crossbred steers were used in an individual feeding trial to evaluate the effects of adding a molasses-fat blend (Synergy® 19/14; Cargill Molasses Liquid Products) to diets at 6 or 12% (dry basis) on growth performance, carcass traits, and feed intake behavior. Dry-rolled corn was processed to a mean geometric particle size of either 2,000 or 3,800 microns. Adding the liquid supplement at 6% to the coarse-rolled finishing ration improved gain (P<.1) and feed efficiency (P<.1). Incorporation of Synergy 19/14 into feedlot rations may help reduce fluctuations in feed intake.
Keywords: Beef; Molasses; Fat; Steers; Finishing; Carcasses